Hyperbaric oxygen improves healing in experimental rat colitis - (:unkn) unknown (UNDERSEA & HYPERBARIC MEDICAL SOC INC, 2002)
Akin, ML, Gulluoglu BM, Uluutku H, Erenoglu. C, Elbuken E, Yildirim S, Celenk T, Hyperbaric: oxygen improves healing in experimental rat colitis. Undersea Hyperb Med 2002; 29(4):279-285 - This study was designed to investigate therapeutic effects of hyperbaric oxygen on experimentally induced colitis in rats by assessing oxidative tissue damage, neutrophil accumulation and histological changes. Six groups of animals were used. No procedures were done in the sham group. In the vehicle group, 50% ethanol-induced colitis, and in four other groups, 2,4,6-trinitrobenzene sulphonic acid-induced colonic inflammation was achieved. In acute and chronic colitis non-treatment groups, no other procedure was done. In acute and chronic colitis hyperbaric oxygen treatment groups, rats underwent hyperbaric oxygen treatment for two or fourteen days. On the third and fifteenth days respectively tissue and blood samples were taken for microscopic and macroscopic damage assessment, myeloperoxidase activity and serum carbonyl content measurements. There was significant colonic tissue damage in non-treatment groups at 48 hours and 14 days. Hyperbaric oxygen treatment ameliorated the macroscopic damage significantly in chronic colitis. Amelioration of microscopic changes was not significant in each hyperbaric oxygen-treated group. Hyperbaric oxygen treatment significantly reduced tissue myeloperoxidase activity in acute colitis and decreased plasma carbonyl content in chronic colitis. In the present study, hyperbaric oxygen treatment Significantly ameliorated trinitrobenzene sulphonic acid-induced chronic colitis in rats.
Keywords: experimental colitis; hyperbaric oxygen; protein oxidation; myeloperoxidase; INFLAMMATORY BOWEL-DISEASE; NITRIC-OXIDE SYNTHASE; ACID-INDUCED COLITIS; THERAPY; ISCHEMIA; REPERFUSION; INHIBITION; INTESTINE